PENDIDIKAN DAN PEMBELAJARAN (HOME SCHOOLI/Ġ) (Suatu Tinjauan Teoritis dan Praktis) - Muhtadi, Ali (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Educational innovation must continues improved, remember stillmuch education problems that have not yet handled properly byconventional method, specially in accomodating difference owned bystudents from character facet, intellegence, background, physicalgrowth, mental, enthusiasm, talent, learns style etc. Existance ofhome schooling education model is must countered as a form ofeducational model alternative and awareness of evocation oldfellows of its responsibility to their children education